The bamA gene for anaerobic ring fission is widely distributed in the environment - Porter, Abigail W.; Young, Lily Y. (Frontiers in Microbiology, 2013)
Benzoyl-CoA is the signature central metabolite associated with the anaerobic metabolism of a diverse range of compounds such as humic acid, lignin, amino acids, and industrial chemicals. Aromatic chemicals with different upstream degradation pathways all funnel into the downstream benzoyl-CoA pathway. Different genes encoding enzymes of the benzoyl-CoA pathway could be used as biomarkers for the anaerobic benzoyl-CoA pathway, however, the ring opening hydrolase, encoded by the bamA gene, is ideal because it is detected under a range of respiratory conditions, including under denitrifying, iron-reducing, sulfate-reducing, and fermentative conditions. This work evaluated DNA samples from six diverse environments for the presence of the bamA gene, and had positive results for every sample. Individual bamA gene clones from these sites were compared to published genome sequences. The clone sequences were distributed amongst the genome sequences, although there were clone sequences from two of the analyzed sites that formed a unique clade. Clone sequences were then grouped by site and analyzed with a functional operational taxonomic unit based clustering program to compare the bamA gene diversity of these sites to that of several locations reported in the literature. The results showed that the sequence diversity of the sites separated into two clusters, but there was no clear trend that could be related to the site characteristics. Interestingly, two pristine freshwater sites formed a subgroup within one of the larger clusters. Thus far the bamA gene has only been examined within the context of contaminated environments, however, this study demonstrates that the bamA gene is also detected in uncontaminated sites. The widespread presence of the bamA gene in diverse environments suggests that the anaerobic benzoyl-CoA pathway plays an important role in the global carbon cycle that has thus far been understudied.